Evaluation of Controls on CV. Baren’s in Koya Koso Village The District Abepura Jayapura City Province Papua - Epres Maling; Pudji Astuty (Publikasi Indonesia, 2023)
Koya Koso mining is one of the group C exploration materials which will be exploitation where mining locations are in Papua Province which is located in Abepura District, Jayapura City, Papua Province with types of gamping materials. The concept of erosion control is a pattern of activity in effort to rehab and use damaged land due to mining activities carried out by the CV. Barend’s, namely excavation, charged, and environmental damage to land. In the principle of erosion control activities are carried out in several stages and the methods that can be used so that the results get better. The stages of evaluation control of erosion starting from soil conservation activities, the selection of land cover vegetation, control pH of soil, manufacturing of panting holes. And until the implementation of the evaluation of erosion control can be done accurately. Erosion control activities that have been planned to start from hoarding activities and replanting (revegetation) originally had links and function to rehab and utilize post-rection land in the company with an area of 1,9 Ha will cover with humus materials with a thickness of 2 m. After hoarding is completed, it will be continued with vegetation activities. For the total cost of the overall reclamation of RP. 15. 824.000; with the length of time reclamation work for approximately 2 moths 15 days.